Nación, representación y articulación territorial del Estado en las Cortes de Cádiz - Suanzes-Carpegna, Joaquín Varela (2023)
In the context of the Courts of Cádiz, and based on the theory of the state, the author studies the nation as a subject and object of political representation, as the subject on which state sovereignty depends. Spain‘s political unity had different meanings in the Courts of Cadiz. The royalist dep uties, defenders of the institutions of the ancien régime, conceived the nation from an organic and estate -based perspective; they saw the nation as a sum of provinces and kingdoms that had to retain their own specific characteristics and self government. The American deputies, as members of a Creole elite, approached the nation from the perspective of territorial organicism, and understood the nation as a sum of independent sovereign units. Finally, the liberal deputies from the metropolis, assuming an individualist point of view, treated the nation as a union of individual wills, a subject made of formally equal individuals who would be represented independently from social or territorial conditions.